Intervensi Senam Kaki Berdasarkan Self Care terhadap Sensitifitas Kaki Pasien Diabetes Melitus - Ariyanto, Topan; Nurharlinah, Nurharlinah; Riyanto, Agus; Inayah, Iin; Safarina, Lina (Journal of Telenursing (JOTING), 2024)
This study aims to identify the effect of self-care based foot gymnastics intervention on foot sensitivity, The method used is Quasi Experimental Design with Pretest Posttest Nonequivalent Control Group Design design that provides pretest before undergoing intervention. Based on the results of statistical tests using the Paired Samples Test, the resulting P value is 0.000 < 0.05, where there is an effect of Foot Exercises Based on Self care on Diabetes Foot Sensitivity in the intervention group before and after the foot exercise intervention based on self care, Conclusion that there is an effect of Self care Based Foot Exercises on Foot Sensitivity. Keywords: Diabetes Mellitus, Foot Sensitivity, Foot Gymnastics, Self Care.